2022
DOI: 10.3389/fcell.2021.775102
|View full text |Cite
|
Sign up to set email alerts
|

Development, Diversity, and Neurogenic Capacity of Enteric Glia

Abstract: Enteric glia are a fascinating population of cells. Initially identified in the gut wall as the “support” cells of the enteric nervous system, studies over the past 20 years have unveiled a vast array of functions carried out by enteric glia. They mediate enteric nervous system signalling and play a vital role in the local regulation of gut functions. Enteric glial cells interact with other gastrointestinal cell types such as those of the epithelium and immune system to preserve homeostasis, and are perceptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 214 publications
(352 reference statements)
0
24
0
Order By: Relevance
“…Chronic hyperglycemia itself and its harmful/protective mechanisms influence neuronal survival in myriad ways [6,40,41]. Besides neuronal death, adult neurogenesis also influences the total enteric neuronal number and the ratio of the different subpopulations (e.g., nitrergic, cholinergic) of the enteric neurons [39,42]. Anitha et al [37] reported that the lack of TLR4 is associated with reduced gastrointestinal motility, and found that these motility problems were caused by damage to the enteric neurons and not the muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic hyperglycemia itself and its harmful/protective mechanisms influence neuronal survival in myriad ways [6,40,41]. Besides neuronal death, adult neurogenesis also influences the total enteric neuronal number and the ratio of the different subpopulations (e.g., nitrergic, cholinergic) of the enteric neurons [39,42]. Anitha et al [37] reported that the lack of TLR4 is associated with reduced gastrointestinal motility, and found that these motility problems were caused by damage to the enteric neurons and not the muscle.…”
Section: Discussionmentioning
confidence: 99%
“…However, these findings need more in-depth investigation, particularly in the context of gastrointestinal cancers. In fact, as the cancerous gastrointestinal tract contains cells with neurogenic potential 103 , future studies need to define whether they contribute to neoneurogenesis in gastrointestinal cancers.…”
Section: ();mentioning
confidence: 99%
“…the ENS neurons is precisely controlled. For additional information on the ENS development, several recent reviews are available for reference (Lake and Heuckeroth, 2013 ; Rao and Gershon, 2018 ; Boesmans et al, 2021 ).…”
Section: Development and Classification Of Egcsmentioning
confidence: 99%